Mineral homeostasis in children with acute lymphoblastic leukemia before and after chemotherapy - Jamal, CY; Karim, MA; Rahman, MH; Rahman, SA; Mannan, MA (Mymensingh Medical Journal, 2011)
Mymensingh Med J. 2011 Apr;20(2): 206-212 The abstract of this article is available on the PubMed website